Blood Pressure, Carotid Flow Pulsatility, and the Risk of Stroke: A Community-Based Study. Issue 9 (September 2016) - Chuang, Shao-Yuan; Cheng, Hao-Min; Bai, Chyi-Huey; Yeh, Wen-Ting; Chen, Jiunn-Rong; Pan, Wen-Harn
Abstract : Background and Purpose—: High blood pressure is a major cause of cardiovascular events, and carotid flow pulsatility may be associated with cardiovascular events. However, the combined effect of blood pressure and flow pulsatility on the development of stroke remains unclear. Therefore, we investigated the combined influence of central blood pressure and pulsatility index (PI) on the incidence of stroke. Methods—: Baseline data from 2033 adults (≥30 years) without stroke history in the Cardiovascular Disease Risk Factor Two-Township Study were linked to incident stroke. Common carotid flow PI was calculated by peak systolic velocity, end-diastolic velocity, and mean vessel velocity, which were measured in the common carotid artery. Hazard ratios for the risk of total stroke resulting from high central systolic blood pressure (CSBP) and high PI were calculated with Cox proportional hazard models. Results—: Over a median follow-up of 9.81 years, 132 people incurred stroke events. The incidence rates of stroke were 1.3, 6.4, and 13.2 per 1000 person-years for tertile groups of CSBP ( P for trend<0.05) and 4.3, 7.0, and 9.4 per 1000 person-years for tertile groups of PI ( P for trend<0.05). Compared with the first tertile of CSBP, hazard ratios were 4.88 (95% confidence interval, 2.29–10.43) for the second tertile and 10.42 (5.05–21.53) for the third tertile. Hazard ratios of PI were 2.18 (1.39–3.42; third tertile) and 1.64 (1.02–2.63; second tertile) compared with the first tertile. The individuals with a high CSBP and high PI had a 13-fold higher stroke risk compared with those with low CSBP and low PI (13.2; 1.75–99.71) after adjusting for age, sex, and traditional cardiovascular risk. Conclusions—: CSBP and common carotid PI jointly and independently predicted future stroke. Carotid flow pulsatility may play an important role in the development of stroke.